Ecological factors associated with fox feces density in an Echinococcus multilocularis endemic zone in Japan - Fukui, Megumi; Uraguchi, Kohji; Numa, Himika; Suzuki, Toru; Karasawa, Michiko; Maita, Kaoruko; Yokozawa, Terumi; Hayama, Yoko; Makita, Kohei (Frontiers in Veterinary Science, 2024)
IntroductionHuman alveolar echinococcosis caused by Echinococcus multilocularis is an important zoonotic disease in the northern hemisphere. The life cycle of E. multilocularis is maintained primarily in wild animals and requires an intermediate host (mainly small mammals). Human can become an intermediate host through accidental ingestion of E. multilocularis eggs. Hokkaido Prefecture is the only area of Japan in which human alveolar echinococcosis is endemic. The purposes of this study were to elucidate the land use ecological factors associated with the density of red fox feces along paved roads and the relationship between the distributions of red fox (Vulpes vulpes) populations and fox feces, which determine the level of hazard from eggs.MethodsA series of surveys was conducted in the central part of the Nemuro Peninsula of Hokkaido, excluding urban areas, over a total of 4 years in May–June in 2014 and 2016–2018 when red foxes remain with their cubs around the dens. Transects of 500 m were set up on paved roads, and feces within the transects were counted. Univariable and multivariable analyses were performed to examine ecological factors including the principal components (PCs) of five land use–type occupancy proportions within 500 m and 1 km, respectively, as explanatory fixed-effect variables. The number of feces in each transect was examined as the response variable using integrated nested Laplace approximation with negative binomial errors with a spatio-temporal autocorrelations structure to separate the effects of similarities of neighboring locations and annual variation. The multivariable models with the lowest widely applicable information criterion values were selected.ResultsThe feces density was explained by the PC of the 500- m buffer (−0.27, 2.5th and 97.5th percentiles: −0.44, −0.10) characterized by mixed forests (−0.82) and scarcity of residential areas (0.29) and the proximity to the nearest livestock farm house (−0.35, 2.5th and 97.5th percentiles: −0.53, −0.17). This suggested that foxes defecate in the areas where prey is abundant, avoiding humans.DiscussionPolicy discussions regarding bait distribution design targeting these conditions should be initiated.